1988
DOI: 10.1073/pnas.85.17.6473
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQ rather than HLA-DR region might be involved in dominant nonsusceptibility to diabetes.

Abstract: Since HLA-DRw15 (a subdivision of the HLA-DR2 specificity previously called DR2 long) is associated with dominant nonsusceptibility to insulin-dependent diabetes mellitus (IDDM), while HLA-DRw16 (another subdivision of HLA-DR2, previously called DR2 short) is positively associated with the disease, we looked for particular characteristics of An increased frequency of some HLA-DR specificities has been reported among patients with insulin-dependent diabetes mellitus (IDDM): DR3, DR4, and, to a lesser extent, DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 24 publications
(37 reference statements)
1
24
0
Order By: Relevance
“…Extensive analysis at the DR locus has shown that the relative risk associated with these alleles is -4-6. When the analysis is performed at the DQ locus, two alleles seem associated with disease: DQw2 (DQBI*0201) and DQw8 (DQBI*0302) (22,26,44,45). In previous studies we demonstrated that approximately one-third of our patients with IDDM are positive only for DQBI *0201, approximately onethird are positive for DQBI *0302, and -25% are positive for both (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive analysis at the DR locus has shown that the relative risk associated with these alleles is -4-6. When the analysis is performed at the DQ locus, two alleles seem associated with disease: DQw2 (DQBI*0201) and DQw8 (DQBI*0302) (22,26,44,45). In previous studies we demonstrated that approximately one-third of our patients with IDDM are positive only for DQBI *0201, approximately onethird are positive for DQBI *0302, and -25% are positive for both (23).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups, including our own, have demonstrated an association of the DQBI*0302 allele with an increased risk for the development of IDDM, whereas other alleles (i.e., DQBI*0602) were associated with protection (21)(22)(23)(24)(25)(26). In subsequent studies it was determined that there was little association with known DP alleles and susceptibility to IDDM (25).…”
mentioning
confidence: 99%
“…Among Caucasians, the disease is positively associated with DR3 and DR4 and negatively associated with DR2 (3)(4)(5). Recently, on the basis of restriction length fragment polymorphism (RFLP) and oligonucleotide typing, the notion has emerged that IDDM susceptibility or resistance is preferentially associated with a limited number of alleles of the HLA-DQB locus (6)(7)(8)(9)(10). Susceptibility has also been assigned to DQB1 alleles encoding amino acids other than aspartic acid (Asp) at position 57 of the DQI3 chain (11 -14).…”
Section: Introductionmentioning
confidence: 99%
“…14 The apparent decrease in transmission of the 87-bp allele could reflect one of two things. First, the allele might actually be protective, as has been suggested for HLA-DQ or HLA-DR in IDDM 15 and Apo E2 in Alzheimer's disease. 16,17 In both these examples, molecular models based on the changes in protein have been proposed to account for protective effects.…”
mentioning
confidence: 99%